Use And Misuse Of Antimicrobial Agents In Healthcare Settings Of Diyala Province - Al-Salihy, Shaima'a R; Rashid, Ibraheem M (Diyala Journal of Medicine, 2018)
Background: Antibiotics are among the most highly misused and irrationally prescribed medicines by health professionals, which directly contribute to the drug resistance problem. Objective: To evaluate the rates of irrational antibiotic prescription in Baquba and Al-Batool Teaching hospitals. Patients and Methods: This study was conducted in Baquba and Al-Batool Teaching Hospitals during the period from 1st December 2015 to 1st March 2016. Two- hundred and fifty-five randomly selected patients present to the internal medicine wards in emergency departments due to different causes were tested for antibiotic misuse. All of the medication prescribed were reported, reviewed and carefully assessed according to the standard criteria. Results: This study revealed that (78.4%) of patients had been medicated with antibiotics in rate of 100% of irrational use. Cephalosporins score the higher rate (35.3%) in prescription followed by penicillins (23.5%). The most frequent indications for antibiotics prescribed wereUrinary Tract Infections (UTI) with 51(25.5%) followed by Upper and Lower Respiratory Tract Infections (URTI, LRTI) with (48 %, 46%), respectively. Conclusion: The rate of antibiotic misuse is unacceptably high. The antibiotics prescription need further evaluation to reduce unnecessary prescription.